Czech inscriptions in the urban space of Racibórz - Wachowska, Victoria (Mundus Slavicus I, 2025)
The aim of this research is to document Czech inscriptions found in the urban space of Racibórz. For centuries, Racibórz was within the borders of the Kingdom of Bohemia, which fostered close relations with the Principality of Opava. Today, Opava and Racibórz maintain ties through a twin-town partnership, promoting the integration of both regions. This study focuses on written messages on static media located in the very center of Racibórz. The inscriptions are found both on external plaques mounted on buildings and on those located inside. The inscriptions have been categorized into three groups: plaques, museum texts, and advertisements.